The Role of Technology in Transforming Classroom Instruction: An Analysis of Blended Learning Approaches - Hanafi, Imam; Alijoyo, Franciskus Antonius; Amin, Husna; Sudarsono, Bernadus Gunawan; Damayanto, Antonio (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This research explores how technology has changed teaching methods in the classroom through a blended learning approach. The research method used in this study is literature studies, which look for references appropriate to the research context. The study's findings suggest that technology can increase student engagement, facilitate access to a wider range of learning activities, and improve learning outcomes through more interactive and flexible methods. When strategically integrated into the learning process, technology improves teaching efficiency and prepares students with the skills needed for the digital age. The implications of these findings are important for education stakeholders in designing and implementing teaching practices that harness the potential of technology to improve the learning process in the classroom. Further research is suggested to conduct empirical studies involving experiments in real classrooms to measure the direct impact of technology and blended learning approaches on student engagement and learning outcomes.